Perancangan Ulang Tata Letak Pasar Johar Baru untuk Mengurangi Kepadatan Lalu Lintas dalam Pasar - Helena Sisilia Ratna Soetopo; Hendy Tannady; Filscha Nurprihatin; Panca Jodiawan (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
The existance of Traditional Market is still irreplacable even by Modern Market which grow rapidly in this decade. This result comes from an observation showing that a lot of people still come and do transactions in Traditional Market. Johar Baru Market is of Traditional Market located in Central Jakarta. This market is supposed to accomodate 43.509 citizens who live in Administrative Village Johar Baru, Central Jakarta. The research utilizes data mining, particularly Market Basket Analysis methods to find the pattern of product sets association. From analyzed pattern, the research is continued by determining the eficient and efective layout in hope of reducing any congestions occured in Market. The result is to group vegetable sellers which currently spread over 17 blocks into 9 blocks and are placed at south of the market, to group fruit sellers which currently spread over 9 blocks into 4 blocks and are placed at south of the market, to group chicken sellers which currently spread over 7 blocks into 5 blocks and are placed at west of the market, to group meat sellers which currently spread over 5 blocks into 4 blocks and are placed at north of the market, to group fish sellers which currently spread over 7 blocks into 4 blocks and are placed at west of the market, to group primary substance sellers which currently spread over 13 blocks into 6 blocks and are placed at east of the market, to group Tofu and Fermented Soybean sellers which currently spread over 7 blocks into 3 blocks and are placed at east of the market, to group coconut sellers which currently spread over 3 blocks into 2 blocks and are placed at north of the market, to group food sellers which currently spread over 8 blocks into 5 blocks and are placed at east of the market, and to group processed food sellers which currently spread over 4 blocks into 2 blocks and are placed at north of the market.Keywords: Johar Baru Market, Traffic Density, Market Basket Analysis